(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The current study aimed to know the extent of the effect of silymarin and its usefulness on the productive performance and some characteristics of the carcass of broilers which consuming diets containing aflatoxins which counteract the effects of negative toxins, which is One hundred and forty-four male broiler chicks, type (ROSS 308), one day old, of similar weights (40 + 5g), were distributed into four groups of equal number by 36 birds per group, which in turn was divided into three replicates by 12 birds for each duplicate. In the following figure, the first group (the control group), the second group (the standard diet plus aflatoxin in an amount of 500 micrograms/ kg of feed), the third group (the standard diet plus aflatoxin in an amount of 500 micrograms/ kg of feed in addition to 0.5 ml of silymarin per 1 liter of drinking water), the fourth group (the standard ration plus aflatoxin in an amount of 500 micrograms / kg of feed in addition to 1 milliliter of silymarin per 1 liter of drinking water). Ground culture was used on a deep litter, the experiment lasted for (35 days). During the trial period, the characteristics of the production performance for a period of five weeks were calculated, which are body weight, amount of feed consumed, weight gain rate, and feed conversion ratio. The results showed a mathematical and significant improvement in favor of the fourth group compared to the rest of the groups. On the last day of the experiment, five chicks were slaughtered from each replicate. The carcass characteristics were measured and the proportions of the following organs were studied: the pancreas, the gizzard, the liver, the spleen, the heart, and the stomach. The results showed that there were no significant differences between the four groups in most of the carcass characteristics, despite some slight improvement in some of the carcass characteristics. It is concluded from this study that adding silymarin to drinking water for groups of male broilers consuming aflatoxin may improve some of their productive characteristics.